Conditions for the Introduction of Regulation for Short-Term Rentals - Brezina, Vilim; Polívka, Jan; Stark, Martin (Critical Housing Analysis, 2021)
Most cities in major agglomerations in Europe started to address the rise of short-term accommodation rentals by introducing regulation designed to protect the local housing stock. The momentum behind the widespread introduction of such regulations can be attributed to qualitative and quantitative factors. This article examines selected fields related to short-term rentals in order to uncover the (structural) triggers or conditions that are necessary and sufficient for municipalities to initiate the regulation of their housing market. The study is based on the systematic examination of the effects of those triggers and their combinations using qualitative comparative analysis (QCA). With this method, we explore the implementation or non-implementation of regulation on a sample of major German cities. The results suggest a universal set of conditions covering three central fields: housing market situation, accommodation market conditions and tourism accommodation demand.